Design and preparation of N-linked hydroxypyridine-based APJ agonists. (1st October 2022) - Richter, Jeremy M.; Alex Bates, J.; Gargalovic, Peter; Onorato, Joelle M.; Generaux, Claudia; Wang, Tao; Gordon, David A.; Wexler, Ruth R.; Finlay, Heather J.
Graphical abstract: Abstract: Agonism of the apelin receptor (APJ) has demonstrated beneficial effects in models of heart failure. We have previously disclosed compounds such as 4, which showed good APJ agonist activity but were metabolized to the mono-demethylated, non-interconverting atropisomer metabolites. Herein, we detail the design and optimization of a novel series of N-linked APJ agonists with good potency, metabolic stability, and rat pharmacokinetic profile, which are unable to undergo the same metabolic mono-demethylation cleavage.